(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: United Nations World Volunteerism report of 2018 highlights that around 110 million individuals engage in volunteer program all over the world, out of which thirty percent involve through formal organisation and the other seventy percent participate in informal volunteerism. Although there is a steady increase in the volunteer’s engagement globally, it is also vital to understand the key driving factor to choose an organisation, contribution and involvement in projects as well as their resilience in the community engagement at a micro-level. Even though socio-cultural, psycho logical and behavioural aspects of voluntourism or volunteering tourists have been studied directly, literature on the Indian context is rarely found. Objective: This paper outlines motivation, experience, satisfaction and revisit intentions of tourists participate in voluntourism in Puducherry. Methodology: For analysing the same, the authors have taken two organizations (Sristi Village and Atmasanga Environment Alliance) for an extensive primary survey. Data analysis and statistical tests were performed using IBM SPSS and IBM SPSS Amos SEM (Structural Equation Modeling) tools. Results: The present study confirmed the findings of three antecedents of voluntourists such as ‘Motivation, Experience, and Satisfaction’ for understanding volunteers’ intention to revisit a volunteered organisation along with future partici pation in other volunteering program and recommendation. Taken together, these results suggest that the overall revisit intention is dependent on all the factors included in the study. The study also revealed that the volunteers aged between (31-40) had a major impact on motivation. Taken together, these results suggest that the overall revisit intention is de pendent on all the factors included in the study. Conclusion: These observations have many implications for research into awareness and effectiveness of the voluntourists projects to all stakeholders.